Familial testicular germ cell tumors (FTGCT) – overview of a multidisciplinary etiologic study. (9th October 2014) - Greene, M. H.; Mai, P. L.; Loud, J. T.; Pathak, A.; Peters, J. A.; Mirabello, L.; McMaster, M. L.; Rosenberg, P.; Stewart, D. R.
Summary: This Review summarizes the cumulative results of the National Cancer Institute Clinical Genetics Branch Multidisciplinary Etiologic Study of Familial Testicular Germ Cell Tumors (FTGCT). Initiated 12 years ago, this protocol enrolled 724 subjects from 147 unrelated families with either ≥2 affected men ( n = 90) with TGCT or a proband with bilateral TGCT and a negative family history for this cancer ( n = 57). Data were collected directly from 162 subjects evaluated at the NIH Clinical Center, and 562 subjects provided information from their home communities (Field Cohort). The primary study aims included (i) ascertaining, enrolling eligible FTGCT kindred, (ii) characterizing the clinical phenotype of multiple‐case families, (iii) identifying the underlying genetic mechanism for TGCT susceptibility in families, (iv) evaluating counseling, psychosocial, and behavioral issues resulting from membership in an FTGCT family, and (v) creating an annotated biospecimen repository to permit subsequent translational research studies. Noteworthy findings include (i) documenting the epidemiologic similarities between familial and sporadic TGCT, (ii) demonstrating significantly younger age‐at‐diagnosis for familial vs. sporadic TGCT, (iii) absence of a dysmorphic phenotype in affected family members, (iv) shifting the focus of gene discovery from a search for rare, highly penetrant susceptibility variants to the hypothesis that multiple, more common, lower penetrance genes underlie TGCT genetic risk, (v) implicating testicular microlithiasis in FTGCT risk, and (vi) observing that aberrant methylation may contribute to FTGCT risk. A clinically based, biospecimen‐intensive, multidisciplinary research strategy has provided novel, valuable insights into the etiology of FTGCT, and created a research resource which will support FTGCT clinical and laboratory studies for years to come.